Benchmarking early literacy skills: developing a tool - Kothari, Brij; Joshi, Ashok (2002)
India's literacy rate has been rising gradually. Unfortunately we are in the dark about the literacy levels of the so-called literates. This paper attempts to describe a simple, quick, and easy to administer tool for measuring literacy skills. The tool has been found to be useful in literacy and primary education contexts. Its use on a sample population can throw light on the distribution of literates along a range of skill levels. - Reproduced.
Keywords: Literacy - India; Literacy